Epindolidiones-Versatile and Stable Hydrogen-Bonded Pigments for Organic Field-Effect Transistors and Light-Emitting Diodes - Glowacki, Eric Daniel; Romanazzi, Giuseppe; Yumusak, Cigdem; Coskun, Halime; Monkowius, Uwe; Voss, Gundula; Burian, Max; Lechner, Rainer T.; Demitri, Nicola; Redhammer, Guenther J.; Sunger, Nevsal; Suranna, Gian Paolo; et al. (WILEY-V C H VERLAG GMBH, 2015)
Hydrogen-bonded pigments are remarkably stable high-crystal lattice energy organic solids. Here a lesser-known family of compounds, the epindolidiones, which demonstrates electronic transport with extraordinary stability, even in highly demanding aqueous environments, is reported. Hole mobilities in the range 0.05-1 cm(2) V-1 s(-1) can be achieved, with lower electron mobilities of up to 0.1 cm(2) V-1 s(-1). To help understand charge transport in epindolidiones, X-ray diffraction is used to solve the crystal structure of 2,8-difluoroepindolidione and 2,8-dichloroepindolidione. Both derivatives crystallize with a linear-chain H-bonding lattice featuring two-dimensional - stacking. Powder diffraction indicates that the unsubstituted epindolidione has very similar crystallinity. All types of epindolidiones measured here display strong low-energy optical emission originating from excimeric states, which coexists with higher-energy fluorescence. This can be exploited in light-emitting diodes, which show the same hybrid singlet and low-energy excimer electroluminescence. Low-voltage FETs are fabricated with epindolidione, which operate reliably under repeated cyclic tests in different ionic solutions within the pH range 3-10 without degradation. Finally, in order to overcome the insolubility of epindolidiones in organic solvents, a chemical procedure is devised to allow solution-processing via the introduction of suitable thermolabile solubilizing groups. This work shows the versatile potential of epindolidione pigments for electronics applications.
Keywords: hydrogen-bonds; organic semiconductors; indigoids; organic electronics; organic field-effect transistors; organic pigments; OPTICAL PROBES; FILMS; INDIGO; QUINACRIDONES; STATES; Chemistry; Science & Technology - Other Topics; Materials Science; Physics